2018
DOI: 10.21775/cimb.029.023
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Gene Transfer in Thermus spp.

Abstract: The small amount of genetic content in thermophiles generally limits their adaptability to environmental changes. In Thermus spp., very active horizontal gene transfer (HGT) mechanisms allow the rapid spread of strain-specific adaptive gene modules among the entire population. Constitutive expression of a rather particular and highly efficient DNA transport apparatus (DTA) is at the center of this HGT-mediated enhanced adaptability. The function of the DTA is dependent on the integrity and longevity of the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
(91 reference statements)
2
10
0
Order By: Relevance
“…This suggests a major role for the chromosome in coding for conserved core functions, which would act as a major counterselection factor if genes were interrupted by IS transposition. Also, our data are in agreement with the more flexible character of the megaplasmids, which encode adaptive and HGT-prone faculties that are only needed under specific conditions [30]. Our data are consistent with other observations of higher incidence of transposable elements within plasmids [47,48], and also that pTT27 harbors the highest plasticity with low synteny among strains [49].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This suggests a major role for the chromosome in coding for conserved core functions, which would act as a major counterselection factor if genes were interrupted by IS transposition. Also, our data are in agreement with the more flexible character of the megaplasmids, which encode adaptive and HGT-prone faculties that are only needed under specific conditions [30]. Our data are consistent with other observations of higher incidence of transposable elements within plasmids [47,48], and also that pTT27 harbors the highest plasticity with low synteny among strains [49].…”
Section: Resultssupporting
confidence: 91%
“…In this way, a few cases of active ISs have previously been reported in T. thermophilus , including IS1000B in strain HB8 [33,34] and ISTth7 in strain HB27 [35]. However, more recent genomic data suggest that a much greater frequency of transpositional events than initially though takes place in the genus [30].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, although evolving in the same ecological niche, the two bacterial species might have adapted differently with respect to their key functions, as has been described previously (de la Haba et al, 2019 ). Since strain RK1 has large strain-specific genomic attributes that may be phage induced, as has already been documented for many rapidly evolving bacterial genomes (Lopez et al, 2012 ; Blesa et al, 2018 ), we wanted to look for CRISPR elements. While genomes of all three strains except P. composti DSM 22900 harbored CRISPR elements ( Supplementary Table 1 ), only one CRISPR from P .…”
Section: Resultsmentioning
confidence: 99%
“…In an extensive search for a physiological role of Ppol, we found that Ppol acted as a barrier against the DNA acquired by the highly efficient natural competence apparatus of this bacterium (Blesa et al ., 2018), in such a way that mutants lacking Ppol (either insertional or marker free) showed an increased transformability of orders of magnitude, not only with replicative and suicide plasmids (Fig. 5) but also with lineal isogenic DNA (Fig.…”
Section: Discussionmentioning
confidence: 99%